2017
DOI: 10.1186/s12967-017-1140-9
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma antigen-specific effector T cell cytokine secretion patterns in patients treated with ipilimumab

Abstract: Background In a previously reported study, patients with regionally advanced melanoma were treated with neoadjuvant ipilimumab (ipi) (Tarhini in PLoS ONE 9(2): e87705, 3). Significant changes in circulating myeloid derived suppressor cells (MDSC), regulatory T cells (Treg) and peptide specific type I CD4+ and CD8+ T cells were noted at week 6 that correlated with clinical outcome. Characterization of antigen-specific effector T cell secreted cytokines may shed insights into ipi associated T cell activation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Although different vaccination trials have reported a lack of a real advantage in the anti-tumor efficacy, 29 , 30 also in combination with the CTLA-4 blockade, 31 the gp100 209-217 (210M)-based vaccination, in combination with IL-2, showed clinical benefits in metastatic melanoma patients. 32 , 33 At TCR level, Schrama et al found the expansion of an oligoclonal gp100 210M-specific TCR repertoire from two patients receiving DTIC alone or in combination with low doses of IFN-α.…”
Section: Discussionmentioning
confidence: 99%
“…Although different vaccination trials have reported a lack of a real advantage in the anti-tumor efficacy, 29 , 30 also in combination with the CTLA-4 blockade, 31 the gp100 209-217 (210M)-based vaccination, in combination with IL-2, showed clinical benefits in metastatic melanoma patients. 32 , 33 At TCR level, Schrama et al found the expansion of an oligoclonal gp100 210M-specific TCR repertoire from two patients receiving DTIC alone or in combination with low doses of IFN-α.…”
Section: Discussionmentioning
confidence: 99%
“…Bead-based arrays find broad applications in cancer research, including melanoma research. Immunotherapeutic predictive or prognostic values of serum cytokines were tested in melanoma patients treated by adjuvant interferon [ 128 ] and ipilimumab [ 69 ]. Blood plasma cytokines have been analysed in patients with unresectable in-transit extremity melanoma, treated by isolated limb infusion with melphalan [ 129 ].…”
Section: Cytokine Detection Techniquesmentioning
confidence: 99%
“…In a study of therapeutic effects of ipilimumab (monoclonal antibody targeting CTLA-4), an increased secretion of IL-1β, IL-2, IL-4, IL-5, IL-7, IL-8, IL-10, IL-13, IL-17, Granulocyte-colony stimulating factor (G-CSF), Granulocyte-macrophage colony-stimulating factor (GM-CSF), HGF, IFNγ, Monocyte chemoattractant protein 1 (MCP-1, CCL2) and VEGF from peripheral blood mononuclear cells (PBMCs) showed a trend towards better recurrence free survival in melanoma [ 69 ]. Interestingly, these cytokines belong to various functional groups with pro-inflammatory and anti-inflammatory effects [ 69 ]. Possibilities of therapeutic administration of cytokines to induce anti-tumour responses in melanoma have been reviewed by Xu et al [ 70 ].…”
Section: Introduction To Melanoma and Cytokinesmentioning
confidence: 99%
“…In addition, the combination of ipilimumab and nivolumab has been approved in patients without B-Raf proto-oncogene, serine/threonine kinase (BRAF) activating mutations and metastatic or unresectable melanoma. Checkpoint regulators on T cells play vital roles in limiting adaptive immune responses and preventing autoimmune and auto-inflammatory reactivity in the normal host (Najjar et al, 2017). In cancer patients, PD-1 expression can be very high on T cells in the tumor microenvironment, and PD-L1, its primary ligand, is variably expressed on tumor cells and antigen-presenting cells within tumors, providing a potent inhibitory influence within the tumor microenvironment.…”
Section: Resultsmentioning
confidence: 99%